Effect of Annealing Temperature on Thermal Behaviour and Crystallinity of Zinc Oxide Supported Magnesium Aluminate (ZnO/MgAl2O4) Via Green Synthesis One Pot Fusion - N.S. Sukiman; M.F. Zavawi; N. Rahmat; M.M. Al-Bakri Abdullah (Archives of Metallurgy and Materials)
Zinc oxide-supported magnesium aluminate (ZnO/MgAl2O4) was synthesized by the one-pot fusion method, consuming magnesium nitrate, aluminum nitrate, and citric acid as starting precursors. The samples prepared were annealed at temperatures ranging from 700 to 900°C to study the influence of annealing temperature on thermal behaviour and crystalline properties. The thermal behaviour of ZnO/MgAl2O4 was characterized by thermogravimetric analysis (TGA), while the structural properties and crystalline phase of ZnO/MgAl2O4 were analysed by X-ray diffraction (XRD). The TGA results show that there were three stages of decomposition in the sample. The first stage indicates the removal of water content from the sample; the second stage indicates the decomposition of citric acid; and the third stage represents the crystallization phase formation at a temperature range of 800- 950°C. The percentage of citric acid decomposition increases with increasing annealing temperatures up to 800°C. However, the decomposition rate gradually reduces at annealing temperatures between 850 and 900°C. XRD analysis results suggest that microstructured ZnO/MgAl2O4 with high crystallinity can be obtained at the highest annealing temperature. It can be concluded that the result of thermal behaviour represented by the decomposition stage is corroborated with structural and crystalline properties at increasing annealing temperatures.